2013
DOI: 10.1128/aem.03893-12
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Occurrence of Extended-Spectrum Beta-Lactamase- and Transferable AmpC Beta-Lactamase-Producing Escherichia coli on Domestic Chicken Meat in Sweden

Abstract: b Forty-four percent of Swedish chicken meat fillets were contaminated with extended-spectrum or transferable AmpC beta-lactamase-producing Escherichia coli strains. Isolates from Swedish chicken meat and broilers were closely related to isolates from chicken meat imported into Sweden; these results indicate a common source of the contamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 26 publications
0
35
1
Order By: Relevance
“…The inability to persist on animal level might be due to an unsuccessful combination of CMY-2-E. coli on plasmid IncA/C. In European broiler meat, CMY-2-E. coli is often found in combination with plasmids IncI1 or IncK (Borjesson et al, 2013;Egervarn et al, 2014). The low occurrence and the observed decrease in this study may suggest that plasmid IncA/C is less able to conjugate and spread in bacterial populations as was previously described for Salmonella (Poole and Crippen, 2009).…”
Section: Resultscontrasting
confidence: 45%
“…The inability to persist on animal level might be due to an unsuccessful combination of CMY-2-E. coli on plasmid IncA/C. In European broiler meat, CMY-2-E. coli is often found in combination with plasmids IncI1 or IncK (Borjesson et al, 2013;Egervarn et al, 2014). The low occurrence and the observed decrease in this study may suggest that plasmid IncA/C is less able to conjugate and spread in bacterial populations as was previously described for Salmonella (Poole and Crippen, 2009).…”
Section: Resultscontrasting
confidence: 45%
“…Our results showed that 96.5 % of the ESBL-E. coli isolates encoded genes of the CTX-M group with or without TEM-encoding genes, suggesting the emergence of the CTX-M gene group as the main contributor to the antibiotic resistance of ESBL-E. coli in food, foodproducing animals, healthy people, and patients not only in developed countries but also in underdeveloped countries (Sasaki et al 2010;Overdevest et al 2011;Börjesson et al 2013;Chen et al 2014;Nakayama et al 2015).…”
Section: Discussionmentioning
confidence: 96%
“…These organisms could serve as a reservoir for the genes encoding antimicrobial resistance, which is transferred to the pathogenic bacteria or transmitted to the human by direct exposure to animals or via the food chain. [15][16][17][18][19] It has been shown that the resistant bacteria with animal origin can either colonize or cause infection in humans.…”
Section: Introductionmentioning
confidence: 99%